PENINGKATAN PERILAKU MORAL ANAK MENGGUNAKAN METODE BERCERITA DENGAN MEDIA GAMBAR PADA USIA 5-6 TAHUN - Irawati, . (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract This research is based on the problem of children aged 5-6 years in PAUD Integrated Cheers Kakap River District Kubu Raya where from all children who are the subject of this study has not shown improvement in the development of good moral behavior. This form of research is a classroom action research using storytelling method. Research subjects are teachers and children who numbered 20 anak.Berdasarkan peniltian results that have been done and after conducted data analysis, generally drawn the conclusion that through the method of storytelling with the media images can improve the development of moral behavior of children from speaking honest, polite and speech, And help each other out. Keyword : Moral behavior, story telling method with image media.